2017
DOI: 10.1111/jvim.14869
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐Enhanced Ultrasound Examination for the Assessment of Renal Perfusion in Cats with Chronic Kidney Disease

Abstract: BackgroundContrast‐enhanced ultrasound examination (CEUS) is a functional imaging technique allowing noninvasive assessment of tissue perfusion. Studies in humans show that the technique holds great potential to be used in the diagnosis of chronic kidney disease (CKD). However, data in veterinary medicine are currently lacking.ObjectivesTo evaluate renal perfusion using CEUS in cats with CKD.AnimalsFourteen client‐owned cats with CKD and 43 healthy control cats.MethodsProspective case‐controlled clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Therefore, the blood velocity parameter, time‐to‐peak, may be useful in detecting early changes in renal perfusion related to the development of chronic kidney disease. In human patients with diabetic nephropathy and cats with chronic kidney disease, time‐to‐peak was significantly prolonged compared to healthy individuals . Future studies are warranted to investigate whether time‐to‐peak is a suitable contrast‐enhanced ultrasound parameter for discriminating between healthy and chronic kidney disease dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the blood velocity parameter, time‐to‐peak, may be useful in detecting early changes in renal perfusion related to the development of chronic kidney disease. In human patients with diabetic nephropathy and cats with chronic kidney disease, time‐to‐peak was significantly prolonged compared to healthy individuals . Future studies are warranted to investigate whether time‐to‐peak is a suitable contrast‐enhanced ultrasound parameter for discriminating between healthy and chronic kidney disease dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The first author performed all analyses after receiving training in contrast‐enhanced ultrasound quantification. The quantification protocol was adapted from previous studies . Based on the high intra‐observer agreement of contrast‐enhanced ultrasound perfusion quantification described by Wei et al., measurements on the video clips were performed once, consecutively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to be a cost-effective modality for evaluating renal function impairment (RFI) [6]. Studies have shown that contrast-enhanced US is almost as sensitive as radioisotope renography in the quantitative diagnosis of chronic renal insufficiency, and correspondingly, contrast-enhanced US could be a useful tool for the assessment of renal function in children with UPJO [7][8][9]. Ionizing radiation exposure is a known risk factor for patients with leukaemia and brain tumours, especially for children with a higher radiation sensitivity and longer life expectancy [10,11].The European Federation of Societies for Ultrasound in Medicine and Biology( EFSUMB)release guidelines state that intravenous CEUS is safe and effective in paediatric populations and can be used effectively to avoid ionizing radiation exposure [11].…”
Section: Introductionmentioning
confidence: 99%
“…Invited speaker Steven Freear from the Universtiy of Leeds spoke about ultrafast plane-wave imaging for nonlinear detection of therapeutic microbubbles [5]. Katrien Vanderperren from Ghent University gave a presentation on contrast-enhanced ultrasound of kidneys in hyperthyroid cats [6]. Erik Verboven from Ghent University presented a study on ultrasound-based dosimetry for radiotherapy, including the in-vitro and in-vivo proof-of-principle.…”
mentioning
confidence: 99%